2020
DOI: 10.1002/jcp.30060
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive landscape of STEAP family functions and prognostic prediction value in glioblastoma

Abstract: Glioblastoma (GBM) is the most common, malignant, and deadly primary glioma. Six‐transmembrane epithelial antigen of prostate (STEAP) family is involved in tumorigenesis; here, we have explored the biological function and the prognostic value of the STEAP family in GBM. Differentially expressed STEAP genes in tumor and normal samples were screened by using The Cancer Genome Atlas (TCGA) database. Univariate and multivariate Cox regression identified the prognosis‐related genes: STEAP2 and STEAP3, which were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 35 publications
(47 reference statements)
4
37
0
Order By: Relevance
“…No significant differences were detected in radiotherapy status. Similar results were also reported by Chen et al [ 30 ].…”
Section: Resultssupporting
confidence: 92%
“…No significant differences were detected in radiotherapy status. Similar results were also reported by Chen et al [ 30 ].…”
Section: Resultssupporting
confidence: 92%
“…STEAP members have been identified as important metalloreductases in vivo and been shown to play a role in iron homeostasis [ 48 ]. They have also been shown to have precise performance in predicting the outcomes of glioma patients [ 49 ]. However, the STEAP family focused on survival time rather than response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The expression STEAPs also exhibits an upregulation in tumors and they can promote tumor cell proliferation as well as suppress apoptosis (70)(71)(72)(73), for example, STEAP3 promotes glioma cell proliferation, invasion, and spheroid formation by inducing mesenchymal transformation, promoting TFR1 expression, and activating the STAT3-FoxM1 axis (39); In colorectal cancer, STEAP3 expression is significantly higher in tumor than that in colonic mucosa (74). However, they recently found that silencing lncRNA STEAP3-AS1(the antisense transcript of STEAP3) inhibited the proliferation, migration, and arrested colon cancer cells at the G0-G1 phase cancer cells through upregulation STEAP3 (75).…”
Section: Steapsmentioning
confidence: 99%